Artificial landscape. - Campens, Angelique; Gyselinck, Tine; Turck, Marianne; Verhellen, Olivier; Zoete, Dirk (Sint-Maria-Aalter : vzw Het Betoverd Bos Sint-Maria-Aalter, 2005)
Bellinckx, Ruben ; van Biesen, Stefaan ; Van Caeckenbergh, Patrick ; Cole, Stijn ; Copers, Leo ; Dheedene, Stefaan ; Gyselinck, Tine ; Muller, Fien ; Turck, Marianne ; Vanseveren, Hannes ; Verhellen, Olivier ; Vermeersch, Pieter ; Vermeulen, Angelo ; Volckaert, T.M.C. ; Zoete, Dirk
Nederlands
Exhibition. Artificial landscape. vzw Het Betoverd Bos Sint-Maria-Aalter, 11.09.2005 - 09.10.2005.
boek